1998
DOI: 10.1080/026990598122188
|View full text |Cite
|
Sign up to set email alerts
|

Auditory vs visual speech timing cues as external rate control to enhance verbal intelligibility in mixed spastic ataxic dysarthric speakers: a pilot study

Abstract: Metronome, singing, and board pacing were used as external rate control techniques for the purpose of comparing the effectiveness of auditory and visual speech timing cues for reducing speech rate and increasing intelligibility in three traumatically brain injured mixed spastic-ataxic dysarthric speakers. A single system design with baseline reversal (ABACAD) was used in this preliminary investigation. Results demonstrated statistically significant (p < 0.05) changes in increased speech intelligibility during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 3 publications
1
36
0
Order By: Relevance
“…Recent findings in aphasia rehabilitation suggest that the rhythmic component in Melodic Intonation Therapy might even be as important as the activation of intact righthemispheric speech circuitry through singing (Stahl et al, 2011). Rate control via auditory rhythmic cues has been successfully applied to fluency disorders (e.g., stuttering, cluttering), as well improvements in intelligibility in dysarthria (Lansford et al, 2011;Pilon et al, 1998;Thaut et al, 2001;Van Nueffelen et al, 2009. NMT has an excellent standardized repertoire of evidence-based techniques for speech and language training based on rhythmic entrainment mechanisms (Thaut and Hoemberg, 2014).…”
Section: More Clinical Applications Of Entrainmentmentioning
confidence: 99%
“…Recent findings in aphasia rehabilitation suggest that the rhythmic component in Melodic Intonation Therapy might even be as important as the activation of intact righthemispheric speech circuitry through singing (Stahl et al, 2011). Rate control via auditory rhythmic cues has been successfully applied to fluency disorders (e.g., stuttering, cluttering), as well improvements in intelligibility in dysarthria (Lansford et al, 2011;Pilon et al, 1998;Thaut et al, 2001;Van Nueffelen et al, 2009. NMT has an excellent standardized repertoire of evidence-based techniques for speech and language training based on rhythmic entrainment mechanisms (Thaut and Hoemberg, 2014).…”
Section: More Clinical Applications Of Entrainmentmentioning
confidence: 99%
“…Traditional strategies to enhance intelligibility, such as rate control (Hammen, Yorkston, & Dowden, 1991;Linebaugh & Wolfe, 1984;Pilon, McIntosh, & Thaut, 1998;Turner, Tjaden, & Weismer, 1995) and articulation therapy (Mitsumoto et al, 1998), may prove useful in the early stages of speech decline, but in later stages strategies that focus on the speech signal may not be sufficient. At this stage, the goal of intervention is to optimize communication with the minimum amount of effort on the part of the person with ALS.…”
Section: Introductionmentioning
confidence: 97%
“…This study revealed that apart from individuals with a hypokinetic and ataxic dysarthria, individuals with UUMND and mixed dysarthria may also benefit from rate control. Two other studies reported a positive effect of rate control in a total of 6 individuals with mixed dysarthria [12,18] . These results suggest that the positive effect of rate control is not restricted to hypokinetic and ataxic dysarthria and that various types of dysarthria may benefit from rate control.…”
Section: Characteristics Of Patients Who May Benefit From Rate Controlmentioning
confidence: 99%